Audit of the SIKS-NG Application System for Poverty Data at the Social Services Office of Southwest Sumba Regency - Emeliana Kaka; Friden Elefri Neno; Paulus Mikku Ate (Fakultas Ilmu Komputer, 2026)
The Next Generation Social Welfare Information System (SIKS-NG) is a national application developed by the Ministry of Social Affairs to manage integrated social welfare data (DTKS). This application is the main tool for local governments in collecting, verifying, and updating information on social assistance recipients. However, the effectiveness and reliability of its implementation in the regions is often not optimal, as evidenced by data inconsistencies, slow input processes, and limited user understanding. This study aims to audit the SIKS-NG system at the Social Service Office of Southwest Sumba Regency to assess the maturity level of the system and its compliance with good information technology governance principles. The research method used a qualitative descriptive approach with the COBIT 5 framework as the basis for the audit. Data was collected through observation, interviews, documentation, and questionnaires administered to system users and poverty data managers. The analysis was conducted on the domains in COBIT 5, namely Deliver, Service, and Support (DSS). The audit results showed that the maturity level of the SIKS-NG system was at a defined level (level 3), which means that the process was running according to procedure but was not yet fully documented and consistently monitored. Several aspects, such as data integration, user training, and information security, still need improvement. This research recommends strengthening IT governance policies, improving the quality of operator human resources, and optimizing real-time data-based monitoring and evaluation systems.